Ipse vidit: fotografia antropologica ottocentesca e possesso del mondo - Alberto Baldi (EtnoAntropologia, 2017)
In Italian and foreign anthropological research with a positivist imprinting, photography is conceived as a device to make up for the documenting limitations of language: it is understood that nothing better than the image made scientifically “credible” by the optic and mechanic instrument that creates it can faithfully reproduce the analyzed human gatherings. Natural and colonized environments, people, faces, working activities, handiwork, celebrative uses, everything is captured by the researcher’s lens, in accordance with his /her possessive bulimia of documentation. The picture is therefore far away from its alleged aseptic nature and therefore forcefully enters into the dyadic relationship between the photographer and the photographed subject in a complex game of dependences, subservience, arrogance, reciprocal individual gains that end up in enlarging and above all distorting the documentation purposes and outcomes that we try to mark out within this contribution.